2020
DOI: 10.2991/efood.k.200211.001
|View full text |Cite
|
Sign up to set email alerts
|

Can Natural Products Suppress Resistant Helicobacter pylori to Fight Against Gastric Diseases in Humans?

Abstract: More than 50% of the world's population is infected with Helicobacter pylori. H. pylori is the major causative agent of gastric ulcers and gastric cancer. H. pylori eradication using antibiotics either alone or together with a proton pump inhibitor is the primary strategy to decrease the incidence of gastric cancer. Although eradication therapy is effective, there are significant adverse effects and more importantly, resistance to antibiotics occurs, which represents a major therapeutic challenge. Multiple nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The effect of berries on H. pylori infection is also approved in human trials by using cranberries, which contains active fractions of quercetin and epicatechin [ 50 ]. The randomized, controlled, double-blind multicentric trial carried out in 295 asymptomatic children positive for H. pylori shows that regular or frequent cranberry juice consumption could be helpful therapy in asymptomatic children with H. pylori infections [ 126 ]. Cranberry fruit and its extracts inhibit H. pylori and show anti-adhesive, anti-inflammatory, and antibacterial bioactivities [ 127 ].…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…The effect of berries on H. pylori infection is also approved in human trials by using cranberries, which contains active fractions of quercetin and epicatechin [ 50 ]. The randomized, controlled, double-blind multicentric trial carried out in 295 asymptomatic children positive for H. pylori shows that regular or frequent cranberry juice consumption could be helpful therapy in asymptomatic children with H. pylori infections [ 126 ]. Cranberry fruit and its extracts inhibit H. pylori and show anti-adhesive, anti-inflammatory, and antibacterial bioactivities [ 127 ].…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…On the one hand, these medicines can inhibit H. pylori enzymes such as urease, which decreases the acidity of gastric juice. On the other hand, they can inhibit the adhesion of H. pylori to gastric mucosa [ 57 ]. In addition, some TCMs that play an antibacterial role by targeting biofilms, proteins of the primary metabolism and virulence factors of H. pylori , have received more attention [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This merits exploration regarding treatments that can target these pathways, providing more favorable in ammatory pro les and hopefully reducing AD incidence. One potential treatment route may be a dietary modi cation, which has been demonstrated to affect both obesity and H. pylori infection by modulating the gut microbiome and in ammatory cascades 13,14 . Our previous research has highlighted the role of black raspberries (BRBs) in autoimmune and malignant conditions and found that in certain situations, BRBs and their metabolic components suppress pro-in ammatory markers and foster gut microbiota with less in ammatory pro les.…”
Section: Introductionmentioning
confidence: 99%